Rare Earth Extraction using Solvent Extraction: Which Factor Has the Most Significant Impact? - Nurul Ain, Ismail (Penerbit Universiti Malaysia Pahang, 2020)
Using a two-level factorial design, a study was undertaken to change the parameters impacting the recovery of rare earth from rare earth mixture. The experimental design was used to screen and identify the major contributing aspects to rare earth recovery. The experiment aims to isolate samarium from a mixture of samarium, europium, and gadolinium. Factors involved consist of pH (pH 1 and pH 6), acid type (nitric acid and hydrochloric acid) and concentration (1.0M and 5.0M), mixing duration (30 min and 120 min), feed composition (20% samarium and 80% samarium), type of diluent (hexane and chloroform), temperature (room temperature and 60°C) and organic to aqueous phase ratio (1:1 and 2:1). The results showed that the samarium recovery was in the range of 0.98% to 90.88%. Based on analysis variance (ANOVA), five factors significantly affect the samarium recovery out of eight factors explored. The five factors according to the most significant order are pH> feed composition> organic to aqueous phase ratio>acid concentration>acid type>mixing duration>type of diluent> temperature. Statistical analysis shows that the linear model is significant, with the value of R2 is 0.9886. Based on the statistical data, five significant variables influence the separation of samarium. This research shows that two-level factorial design can anticipate significant variables impacting rare earth separation, particularly samarium, in the solvent extraction process.